2016
DOI: 10.1176/appi.neuropsych.15030059
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Role of HERV-W in Schizophrenia

Abstract: Schizophrenia is a neuropsychiatric disorder of complex etiology. Human endogenous retroviruses (HERVs) have been presented as possible candidates explaining the connections between the genetic, infectious, neurodevelopmental, and neuroinflammatory aspects of schizophrenia, with the human endogenous retrovirus type W family (HERV-W) showing the greatest evidence of association. Studies have identified retroviral nucleotide sequences, envelope and capsid proteins, and elevated transcription of HERV-W elements i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 81 publications
1
10
0
Order By: Relevance
“…Indeed expression of HERV-encoded env (HERV-K, HERV-W, HERV-E) was shown to be immunosuppressive and to promote cancer development, including leukaemia, prostate cancer and breast cancer. Similar correlation was identified between high expression levels of HERV-W-encoded env and some neurological diseases, including multiple sclerosis and schizophrenia [64]. HERV expression can activate the innate immune response, thereby leading to chronic inflammation and potentially contributing to autoimmune diseases.…”
Section: So What? Consequences For the Virus And The Hostsupporting
confidence: 60%
“…Indeed expression of HERV-encoded env (HERV-K, HERV-W, HERV-E) was shown to be immunosuppressive and to promote cancer development, including leukaemia, prostate cancer and breast cancer. Similar correlation was identified between high expression levels of HERV-W-encoded env and some neurological diseases, including multiple sclerosis and schizophrenia [64]. HERV expression can activate the innate immune response, thereby leading to chronic inflammation and potentially contributing to autoimmune diseases.…”
Section: So What? Consequences For the Virus And The Hostsupporting
confidence: 60%
“…In fact, they make up a significant fraction (~8%) of its sequence content 3 4 5 . Many families of HERVs exhibit high transcriptional activity in different human tissues, and both beneficial 6 7 8 and detrimental effects 8 9 10 have been described. Similarly to other endogenous proviruses, they consist of a 5–10 kb sequence which code for viral proteins, flanked by two Long Terminal Repeats (LTRs) (0.3–1.6 kb in length) that contain regulatory elements for viral protein expression 11 .…”
mentioning
confidence: 99%
“…9,10,16 Another study found syncytin-1 mRNA transcription in plasma samples from patients with schizophrenia, suggesting that syncytin-1 can also play a role in schizophrenia. [17][18][19] Collectively, these findings indicate the important role of syncytin-1 in neuroimmune regulation. To the best of our knowledge, there has been no report on the role of syncytin-1 in anti-NMDAR encephalitis pathogenesis.…”
Section: Introductionmentioning
confidence: 68%